(untitled) - Scott, Derek A. (Greenland, 1998)
This report focuses on international agreements regarding the control and prevention of marine pollution, air pollution and nuclear activities, although some reference is also made to the major international agreements dealing with wildlife and protected areas,...
Keywords: Animal migration,Động vật di cư,Migratory birds; Arctic